A semantic and pragmatic approach to verb particle constructions used in cartoons and puns - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Abdeljalil Naoui Khir Virginia Military Institute, USA   ABSTRACT The aim of this paper is to discuss a special type of verb particle construction in English; namely, phrasal verbs used in cartoons and puns. Granted that the meaning of phrasal verbs may range from literal to idiomatic, their use in cartoons is artistically and linguistically exploited through a combination of verbal and non-verbal cues to convey humor, satire and fun. Our assumption is that this combination rests on the premise that a double reading of phrasal verbs in certain cartoons and puns is possible. To illustrate this, a sample of cartoons using phrasal verbs and puns (taken from www.ecenglish.com, English Teacher Online LLC) will be analyzed showing how the correspondence between the cartoon as a visual mode and the phrasal verb as a linguistic form can yield both literal interpretations and idiomatic ones. Phrasal verbs are also shown to violate Gricean maxims and to depend largely, in their interpretation, on extra linguistic factors.